The bidirectional interaction of the gut microbiome and the innate immune system: Implications for chemotherapy‐induced gastrointestinal toxicity. Issue 10 (1st October 2018) - Secombe, Kate R.; Coller, Janet K.; Gibson, Rachel J.; Wardill, Hannah R.; Bowen, Joanne M.
Abstract : Chemotherapy‐induced gastrointestinal toxicity (CIGT) occurs in up to 80% of all patients undergoing cancer treatment, and leads to symptoms such as diarrhoea, abdominal bleeding and pain. There is currently limited understanding of how to predict an individual patient's risk of CIGT. It is believed the gut microbiome and its interactions with the host's innate immune system plays a key role in the development of this toxicity and potentially other toxicities, however comprehensive bioinformatics modelling has not been rigorously performed. The innate immune system is strongly influenced by the microbial environment and vice‐versa . Ways this may occur include the immune system controlling composition and compartmentalisation of the microbiome, the microbiome affecting development of antigen‐presenting cells, and finally, the NLRP6 inflammasome orchestrating the colonic host‐microbiome interface. This evidence calls into question the role of pre‐treatment risk factors in the development of gastrointestinal toxicity after chemotherapy. This review aims to examine evidence of a bidirectional interaction between the gut microbiome and innate immunity, and how these interactions occur in CIGT. In the future, knowledge of these interactions may lead to improved personalised cancer medicine, predictive risk stratification methods and the development of targeted interventions to reduce, or even prevent, CIGT severity.